Dimensions of social order: Empirical fact, analytical framework and boundary concept - Katja Mielke; Conrad Schetter; Andreas Wilde (University of Bonn, Center for Development Research (ZEF), 2011)
The objective of this paper is to stimulate a discussion about the conditions, modes and benefits of non-state-centric socio-political analyses. By introducing the notion of 'social order' the authors attempt to draft a conceptual approach of how to understand political processes and outcomes in a comprehensive way. Referring to some preliminary research results obtained during two years of extensive field and archival research in Afghanistan, Uzbekistan and Tajikistan, the paper embodies, first, a unique attempt at utilizing a number of theories borrowed from the social sciences and, second, a piece of research that has to be seen as work in progress rather than an all conclusive formula. The point of departure is the empirical observation that some kind of 'social order' always exists. We understand 'social order' as the structuring and structured processes of social reality. It is constantly generated by the interplay of worldviews and institutions. Translated into an analytical framework this approach potentially provides a new kind of vocabulary which - if used systematically - bridges different schools of thought in the social sciences as well as between actors in different societal fields related to politics, such as academia, policy-making, and in applied fields. In the case of a successful reception 'social order' - as advocated here - could serve as a trans-disciplinary boundary concept.
Keywords: 330; social order; boundary concept; worldview; institutions; trans-disciplinary approach